ARMYTHMIC ACTIVITY OF MYOCARDIUM AT DIFFERENT STAGES OF ANESTHESIA AND PERI-OPERATIVE PERIOD IN PATIENTS UNDERGOING CHOLECYSTECTOMY - S. A. Sumin; N. A. Volkova; V. P. Mikhin; E. N. Bogoslovskaya; P. A. Eremin (Вестник анестезиологии и реаниматологии, 2019)
Prevention of cardiovascular complications, which often result in fatal events in the peri-operative period, is one of the most crucial issues of modern anesthesiology.The objective: to investigate the changes in arrhythmic activity and conduction disorders during anesthesia and in the peri-operative period in the patients undergoing open cholecystectomy under general anesthesia.Subjects and methods. 57 patients of 60.1 ± 3.8 years old were enrolled in the study; they all underwent planned open cholecystectomy under combined anesthesia with tracheal intubation and artificial pulmonary ventilation. Group 1 consisted of 28 patients suffering from coronary heart disease (CHD) in the form of exertional angina of functional classes of I and II; and Group 2 included 29 patients without CHD. The frequency of episodes of group and polymorphic premature ventricular contractions, supraventricular tachycardia and atrioventricular block of degree II, was analyzed by daily Holter ECG monitoring for certain time periods during anesthesia and the peri-operative period. Stages of the study: I – on the eve of the surgery (18 h); II – within 6 hours before the surgery; III – immediate preparation and induction of anesthesia (62.0 ± 6.7 min); IV – maintenance of anesthesia (57 ± 14 min); V – recovery from anesthesia (48 ± 11 min); VI – the 2nd day after surgery (18 h).Results. A significant increase in the frequency of episodes of group and polymorphic premature ventricular contractions, supraventricular tachycardia and atrioventricular block of degree II, was found out at the stages of induction, maintenance and recovery from anesthesia in patients with CHD and in patients without concurrent cardiovascular disorders. Increased frequency of episodes of group and polymorphic premature ventricular contractions was observed in patients with CHD at the stages of induction and recovery from anesthesia (by 242 and 225%). The highest increase in the frequency of polymorphic premature ventricular contractions was observed in patients with CHD during recovery from anesthesia (by 284%) and in those without cardiovascular pathology at the induction stage (by 461%); the increase in episodes of supraventricular tachycardia was maximum at the induction stage in the patients without cardiovascular pathology (by 291%).Conclusion: Open cholecystectomy in general anesthesia is associated with increased arrhythmic activity and higher conduction disturbances incidence at all stages of anesthesia in patients with coronary heart disease and those without concurrent cardiovascular disorders.